Preoperative localisation techniques in breast conservative surgery: A systematic review and meta-analysis - Moreira, Inês C. (2021)
The preoperative localisation of non-palpable lesions guided by breast imaging is an important and required procedure for breast-conserving surgery. We conducted a systematic review and meta-analysis of the literature on the comparative impact of different techniques for guided surgical excision of non-palpable breast lesions from reports of clinical or patient-reported outcomes and costs.